Practising community-based participatory research : stories of engagement, empowerment, and mobilization - MacKinnon, Shauna (Purich Books, 2018)
"There is increasing pressure on university scholars to reach beyond the "ivory tower" and engage in collaborative research with communities. But what exactly is community-based participatory research (CBPR) and what does engagement look like? This book presents stories about CBPR from Manitoba Research Alliance projects in marginalized communities. Bringing together experienced researchers with new scholars and community practitioners, the stories describe the impetus for the projects, how they came to be implemented, and how CBPR is still being used within the community. By providing space for researchers and their collaborators to share the stories behind their research, this book offers rich insights into the power and practice of CBPR."--